Field notes contributed by Woodward H. Brown, fall 1977 - Brown, Woodward H.et al (1977)
List of birds and locations contributed by Woodward H. Brown with observers William Boller, Richard Mooney, Eugene Armstrong and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed